Analysis of the Effect of Service Quality and Corporate Image on Customer Loyalty at Toko Graha Elektronik in Palembang City Mediated by Customer Satisfaction - Michel Vincencia; Elia Ardyan (Peneliti.net, 2023)
The goal of this study is to investigate how customer satisfaction, a mediating variable, affects the relationship between service quality and corporate image and customer loyalty at Toko Graha Elektronik in Palembang City. Service quality (X1), company image (X2), customer happiness (M), and customer loyalty were the variables examined (Y). SEM-PLS is the analysis program used. With a sample size of 180 respondents, the population in this study consists of Toko Graha Elektronik customers who have made at least two purchases. The findings indicated that customer satisfaction has an impact on service quality, company image has an impact on customer satisfaction, service quality has no impact on customer loyalty, company image has no impact on customer loyalty, customer satisfaction has an impact on customer loyalty, service quality has an impact on customer loyalty through customer satisfaction as a mediating variable, and corporate image has no impact on customer loyalty through customer satisfaction.